2019
DOI: 10.1016/j.atherosclerosis.2019.08.007
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal low density lipoprotein cholesterol goal achievement and cardiovascular outcomes among adult patients with familial hypercholesterolemia: The CASCADE FH registry

Abstract: • Adults with familial hypercholesterolemia in lipid specialty clinics achieve further LDL-C lowering in specialty care but less than half get to LDL-c < 100 mg/dl. • Atherosclerotic event rates remain high, including among those with prior atherosclerotic vascular disease and average LDL-c < 100 mg/dl.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
32
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 67 publications
(34 citation statements)
references
References 26 publications
1
32
0
1
Order By: Relevance
“…In most countries, less than 1% of FH patients are diagnosed (Nordestgaard et al, 2013). Furthermore, treatment for FH is still limited; for example, the CASCADE-FH Registry reported that only 48% of FH patients achieved LDL-C < 100 mg/dl and 22% achieved LDL-C < 70 mg/dl (Duell et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…In most countries, less than 1% of FH patients are diagnosed (Nordestgaard et al, 2013). Furthermore, treatment for FH is still limited; for example, the CASCADE-FH Registry reported that only 48% of FH patients achieved LDL-C < 100 mg/dl and 22% achieved LDL-C < 70 mg/dl (Duell et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, more than 80% of the FH patients with established ASCVD at enrollment experienced a new event over a 10-year period, despite being treated to mean (95%CI) LDL-C 3.0 (2.9, 3.2) mmol/L, which is a 55% reduction compared to the untreated LDL-C of 6.6 (5.3, 7.9) mmol/L. As observed in other trials on treatment LDL-C is much too high in FH, Duell et al reported 2.9 mmol/L using PCSK9 inhibitors in 30% of the patients (Duell et al, 2019), Langslet et al reported 3.2 mmol/ L in 909 FH patients of whom 47% had ASCVD (Langslet et al, 2020) and in another recent trial on FH patients LDL-C was 4.0 mmol/L on conventional treatment (Raal et al, 2020). Taken together, this suggests that a mean LDL-C around 3.0 mmol/L is about as low as it is possible to achieve in real-world practice in patients with FH.…”
Section: Discussionmentioning
confidence: 70%
“…Effect of statins in FH was also investigated in a Dutch study reporting that statins decreased risk of CHD by 76% vs. those not treated (Versmissen et al, 2008). Further, several studies on real world data have shown that few FH subjects achieve their LDL cholesterol (LDL-C) treatment goals (Bogsrud et al, 2019;Duell et al, 2019;Iyen et al, 2019;Perez de Isla et al, 2019). In the most recent of these studies mean LDL-C was decreased to 2.90 mmol/L in specialized lipid clinics (Duell et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the future, adoption of quality measures that includes either appropriate percent lowering of LDL‐cholesterol, such as 50% lowering, and/or specific targets, such as LDL‐c < 70 mg/dl, should be required for those with ASCVD or for higher risk primary prevention. Those at high‐risk need to engage in a risk discussion with their clinician regarding the potential for benefit versus risk for additional cholesterol lowering therapy, such as ezetimibe or PCSK9 inhibitors 24‐28 . Moreover, risk discussions should remind physicians to increase statin intensity as necessary for patients with a history of SH.…”
Section: Discussionmentioning
confidence: 99%